2018
DOI: 10.1021/acs.joc.8b02521
|View full text |Cite
|
Sign up to set email alerts
|

Indolizine-Cyanine Dyes: Near Infrared Emissive Cyanine Dyes with Increased Stokes Shifts

Abstract: Molecular engineering strategies designed to red-shift cyanine dye absorptions and emissions further into the near-infrared (NIR) spectral region are explored. Through the use of a novel donor group, indolizine, with varying cyanine bridge lengths, dye absorptions and emissions, were shifted deeper into the NIR region than common indoline-cyanines. Stokes shifts resulting from intramolecular steric interactions of up to ∼60 nm in many cases were observed and explained computationally. Molecular brightnesses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 42 publications
4
69
0
Order By: Relevance
“…Out of the 39 hits for unsubstituted phenyl rings attached to indolizine, the majority of entries gave reports of varied synthetic procedures and methodologies to obtain these compounds, underlining their importance. The nearinfrared emissive properties of KIVLIN, KIVLOT, KIVLUZ (Gayton et al, 2019) and KENFAN (McNamara et al, 2017) have also been reported. Structural details of compounds such as CAJTAI (Aslanov et al, 1983), EMUTOV (Liu, et al, 2003), FEDQAH (Liu, et al, 2005), GIYLOP (Sonnenschein & Schneider, 1997), ODEFIN (Qian et al, 2006), PNOIZA, PNOIZB, PNOIZE, PNOIZF (Tafeenkov & Aslanov, 1980), ROLKIM (Tafeenkov & Au, 1996) and TIGXOX (Liu, et al, 2007) have also been deposited.…”
Section: Database Surveymentioning
confidence: 88%
“…Out of the 39 hits for unsubstituted phenyl rings attached to indolizine, the majority of entries gave reports of varied synthetic procedures and methodologies to obtain these compounds, underlining their importance. The nearinfrared emissive properties of KIVLIN, KIVLOT, KIVLUZ (Gayton et al, 2019) and KENFAN (McNamara et al, 2017) have also been reported. Structural details of compounds such as CAJTAI (Aslanov et al, 1983), EMUTOV (Liu, et al, 2003), FEDQAH (Liu, et al, 2005), GIYLOP (Sonnenschein & Schneider, 1997), ODEFIN (Qian et al, 2006), PNOIZA, PNOIZB, PNOIZE, PNOIZF (Tafeenkov & Aslanov, 1980), ROLKIM (Tafeenkov & Au, 1996) and TIGXOX (Liu, et al, 2007) have also been deposited.…”
Section: Database Surveymentioning
confidence: 88%
“…Indolizines, and in particular the annulated ones, are frequently found to exhibit useful biological [ 1 , 2 , 3 , 4 , 5 , 6 ] and optical properties [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The synthesis of indolizines usually relies on the reactivity of pyridinium ylides, which can undergo cycloaddition reactions with alkenes [ 15 , 16 , 17 , 18 ] or alkynes [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Domino and multicomponent reactions allow rapid and efficient construction of molecular complexity; they are widely used for the synthesis of natural products and analogues,, pharmaceutical substances, functional materials,, macrocyclizations, Employing these tools for the preparation of fluorophores and electrophores emerged as a useful technique, enabling fast creation of numerous scaffolds with diverse structure and needful properties. Indolizines are indeed sought‐for heterocycles,, which have various applications as biologically active compounds, dyes, molecular probes and sensors . They are also well‐known fluorophores, with some recent examples of multicomponent syntheses .…”
Section: Introductionmentioning
confidence: 99%